GASTRO-INTESTINAL PARASITES OF STRAY PIGS IN AND AROUND NAGPUR CITY - Bhangale, G N; Bendre, M U; Barbadikar, M S; Jumde , P D; Maske , D K (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Fecal samples of 74 stray pigs were examined by standard procedures. The overall infection rate was 83.78 per cent. The eggs/ ova / larvae of Oesophagostomum sp. (20.27%), Ascaris sp. (35.13%), Fasciolopsis buski (13.51%), Trichuris sp. (8.10%), and Taenia sp. (4.05%) were recorded. The cysts and oocysts of Eimeria sp. (14.86%) and Balantidium coli (58.10%) were also observed.